Love Like This (The Romance Chronicles-Book #1) - Sophie, Love (Lukeman Literary, 2017)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....[This is] the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan re: For Now and Forever) "A very well written novel, describing the struggle of a woman to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos (re: For Now and Forever) LOVE LIKE THIS (The Romance Chronicles-Book #1) is the debut of a new romance series by #1 bestselling author Sophie Love. Keira Swanson, 28, lands her dream job at Viatorum, a slick magazine in New York City, as an aspiring travel writer. But their culture is brutal, her boss is a monster, and she doesn't know if she can last for long. That changes when Keira, by a fluke, is handed a coveted assignment and given her big chance: to travel to Ireland for 30 days, witness the legendary Lisdoonvarna festival of love, and to debunk the myth that true love exists. Keira, cynical herself and in a rocky place with her long-term boyfriend, is all too happy to oblige. But when Keira falls in love with Ireland and meets her Irish tour guide, who just may be the man of her dreams, she is no longer sure of anything. A whirlwind romantic comedy that is as profound as it is funny, LOVE LIKE THIS is book #1 in the debut of a dazzling new romance series that will make you laugh, cry, and will keep you turning pages late into the night-and will make you fall in love with romance all over again. Book #2 in The Romance Chronicles is now available for pre-order!
Keywords: Romantika, romány pro ženy